Multi Orientation Footing In Digital Collage Artwork - FARLAN ADRIAN HASAN (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2020)
The phenomenon of singularity in the direction of the footing has used in realizing this concept. The technique used is digital collage basically built a structure that is binary opposition that is top-down opposition where the bottom area has always been a foothold orientation. The existence of this phenomenon can not be separated from the influence of causal law (cause and effect) the gravitational force of the earth which basically causes all objects to have a uniform footing direction, which ultimately also affects human perception in representing images (photographs, paintings, drawings, etc.). This phenomenon of unity of foothold leads to the concept of "multi-orientation foothold" in the creation of digital collage art, which seeks to get out of the rule of unity of foothold while simultaneously undermining the top-down structure of the image. Deconstruction becomes the foundation using photo media with JPEG format. The method used refers to the five stages of creativity from David Campbell (1986: 18-24), namely: 1) Preparation Phase, 2) Concentration, 3) Incubation, 4) Illumination, and 5) Verification / production.